Upaya Meningkatkan Hasil Belajar Pembelajaran Tari Piring Tradisi melalui Metode Drill di Kelas XI. F6 SMA N 14 Padang - Marchel, Qonita Hesthia; Syeilendra, Syeilendra (YASIN, 2024)
The purpose of this study is to know the improvement of learning outcomes of the ancient Piring dance with the experimental method in class XI. F6 SMA N 14 Padang. This type of research is group action research or "classroom action research" which is carried out in 2 cycles with the stages of planning, implementation, observation and reflection. The tools in this study are the researcher himself and the assistance of supporting tools in the form of recording tools, cameras and test results. Data were collected through literature studies, observations, interviews and literature. The data is analyzed with a percentage formula. The results of the study prove that the use of practice methods in learning dance can stimulate students' enthusiasm and performance in the learning process and increase in each session, the average work of students in the first semester is 72.1% with good criteria, in the second term it is 74.7% the average percentage of student learning work with good criteria, in the third term it is 80.8%. After the implementation of cycle II, student learning achievement increased every semester, the average percentage of student academic achievement in the first semester was 85.1% very good, in the second semester it increased to 93.8% which is a very good measure. The results of students' practical skills with an average score of 70.8 to 96% have progressed very well. The results of this study reached the level of 85% which is the minimum level (KKM) so that student activities are effective on student learning outcomes.